(3MGTjI SfGf CafOj Ydi JaSjQ GdHjVGhjs - (3eLghds
(3ChdgG (B:s
(3jG ef CaMe TbGFb GdHdZGA HHOGFY UfGFY GdBjGJ hHYO aeQchR aj PgH cd COjH dHjH Cf GdTQa GdPj dG jOQc HGdCeGfj GdYde GdPj gh CTQa GdUaGJs
(3BNQgG (B:s
(3hEf CTQa GdYdhe hGdehVhYGJ hdG eYdhe CLd hCYdi ef Gddg JYGdi hdG ePchQ CYXe hdG Cced efg adG PcQ CTQa hdG CaVd efgs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs